2009
DOI: 10.1002/lary.20697
|View full text |Cite
|
Sign up to set email alerts
|

Management of patients treated with chemoradiotherapy for head and neck cancer without prophylactic feeding tubes: The University of Pittsburgh experience

Abstract: Objectives/Hypothesis:Mucositis and dysphagia are common complications of chemoradiotherapy (CRT) for head and neck cancer that may necessitate nutritional support with a gastrostomy tube (G‐tube).Methods:We reviewed records of patients who underwent and completed CRT, which included at least one traditional chemotherapeutic, for previously untreated head and neck cancer. G‐tubes were placed as needed. The timing and duration of G‐tube placement and treatment‐related complications and risk factors for long‐ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 22 publications
2
24
0
Order By: Relevance
“…Benefits were of the same magnitude whether the PEG was placed prior to or early in the treatment or later when dysphagia became problematic. This is consistent with the report of McLaughlin et al [6]. The key indications, regardless of timing, appear to be persistent weight loss, dysphagia, and episodes of dehydration despite fluid supplementation during chemotherapy infusions.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Benefits were of the same magnitude whether the PEG was placed prior to or early in the treatment or later when dysphagia became problematic. This is consistent with the report of McLaughlin et al [6]. The key indications, regardless of timing, appear to be persistent weight loss, dysphagia, and episodes of dehydration despite fluid supplementation during chemotherapy infusions.…”
Section: Discussionsupporting
confidence: 88%
“…The chief obstacles they encountered in these patients were esophageal stricture and airway compromise. Since then a small number of reports have appeared in which the risks, complications and benefits of PEG in head and neck cancer have been debated [3][4][5][6][7][8][9]. None of these has examined long-term outcomes nor has data regarding success of failure of PEG for meeting the nutritional needs of patients, which is the chief reason for doing a PEG, during and after treatment for head and neck cancer.…”
mentioning
confidence: 99%
“…However, the major concern on the early PEG-tube could delay the transition to oral nutrition which may lead swallowing muscles disuse protraction [18,19]. Since high doses to the pharyngeal constructor muscles increase the incidence of long term impaired swallowing [30], early insertion may exacerbate the incidence of pharyngeal stenosis and swallowing impairment after curative radiation.…”
Section: Discussionmentioning
confidence: 99%
“…Salas et al [17] reported in their prospective randomized study that prophylactic PEG-tube insertion and early feeding also improves the QoL of LAHNC patients. However, there are still some concerns and uncertainties for early tube insertion, such as tube-related side effects, delaying the transition to oral nutrition and lack of objective parameters for tube removal decision [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…29,30 Although patients prefer PEG over nasogastric tubes, they can become dependent on PEG tubes. 26,27,31,32 More-advanced disease, altered fractionation, and concurrent chemoradiation are associated with a greater dependence on PEG tubes in patients with oropharyngeal cancer. 32 A recent analysis among patients with swallowing disturbances indicates that mortality rates and pneumonia are similar between the different types of feeding tubes (eg, PEG vs nasogastric tubes); the authors reported that PEG tube feeding seemed to be more effective and as safe as nasogastric tube feeding.…”
Section: Feeding Tubesmentioning
confidence: 99%